HDP-a novel heme detoxification protein from the malaria parasite. - Dewal Jani (Public Library of Science (PLoS), 2008)
When malaria parasites infect host red blood cells (RBC) and proteolyze hemoglobin, a unique, albeit poorly understood parasite-specific mechanism, detoxifies released heme into hemozoin (Hz). Here, we report the identification and characterization of a novel Plasmodium Heme Detoxification Protein (HDP) that is extremely potent in converting heme into Hz. HDP is functionally conserved across Plasmodium genus and its gene locus could not be disrupted. Once expressed, the parasite utilizes a circuitous "Outbound-Inbound" trafficking route by initially secreting HDP into the cytosol of infected RBC. A subsequent endocytosis of host cytosol (and hemoglobin) delivers HDP to the food vacuole (FV), the site of Hz formation. As Hz formation is critical for survival, involvement of HDP in this process suggests that it could be a malaria drug target.